THE INFLUENCE OF ORGANIZATIONAL CAPITAL, FIRM SIZE, AND CEO OVERCONFIDENCE ON TAX AVOIDANCE: THE MODERATING ROLE OF GENDER DIVERSITY - Nyoman Putri Nira Paskasheila; I G. A. M. Asri Dwija Putri (ADISAM Publisher, 2025)
Tax avoidance is a corporate strategy aimed at legally reducing tax liabilities by exploiting loopholes in tax regulations. This study aims to examine the influence of organizational capital, firm size, and CEO overconfidence on tax avoidance, while also investigating the moderating role of gender diversity. The research sample consists of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. After detecting and removing outliers, a total of 377 observations were used for analysis. Prior to analysis, several variables were transformed using the natural logarithm to meet the assumption of normality. The data were analyzed using Moderated Regression Analysis (MRA) with the assistance of SPSS software. The results reveal that both organizational capital and CEO overconfidence have a positive and significant effect on tax avoidance, while firm size has a negative and significant effect. Gender diversity significantly moderates the relationship between organizational capital and firm size on tax avoidance, but does not moderate the effect of CEO overconfidence. These findings reinforce agency theory, emphasizing the critical role of internal corporate characteristics and managerial behavior in shaping tax avoidance strategies. This study is expected to provide valuable insights for managers, regulators, and future researchers in understanding the dynamics of tax avoidance in Indonesia.